Analisis Strategi Differensiasi Citra Perusahaan dalam Pemasaran Sebagai Upaya Untuk Menciptakan Keunggulan Bersaing ( Studi Pada PT. Ar Tour & Travel) - Hakim, Muhammad Arif; Faizah, Nur (BISNIS, 2017)
This research is to know: (a) how the image of PT. AR Tour & Travel by service users, (b) how the efforts of PT. AR Tour & Travel in build the image as a form of differentiation marketing, (c) marketing advantages by use dimension of image done by PT. AR Tour & Travel. This research uses descriptive qualitative research method. Data source used is primary data and secondary data. Technique of collecting data with observation, interview, and documentation. Test of data validity use triangulation. The results are: First, some images that apply to the PT. AR Tour & Travel by service users, (a) PT. AR Tour & Travel has an expensive package price, (b) PT. AR Tour & Travel provides the best facilities, (c) PT. AR Tour & Travel is able to provide a manasik that is easily understood and followed by the pilgrims, (d) PT. AR Tour & Travel has a variety of packages that can be adapted to the needs of pilgrims, (e) The employees of PT. AR Tour & Travel has a friendly attitude in service. Second, the efforts made by PT. AR tours & Travel in image building are, (a) utilizing the charismatic image of the leader of the AR Foundation, (b) varying product packages, (c) applying work traditions and culture, (d) maintaining good communication with service users. Third, the advantages of marketing differentiation using image dimension is quite effective, the indication can be seen from the data of the number of service users who always show well.